Leveraging Lighting Color, Temperature and Luminosity for Improving Classroom Learning: - Michael Seth Mott; Teresa R Thomas; Jodie L Burnette (Networks: An Online Journal for Teacher Research, 2013)
This short article addresses a preliminary exploration of a third grade teachers’ action research applied to the use of a dynamic lighting system for improving educational performance in the classroom. Dynamic lighting offers teachers’ four light settings: focus, energy, calm, and normal. Prior research has revealed a positive relationship between dynamic light use and student cognition, motivation and concentration. What is not known is how a teacher should make use of the four settings throughout the day during all of the activities, content-area learning, and transitions in students’ experience. Teacher data (journal entries) was collected for one year. Case study analysis methodology was utilized with the unit of analysis consisting of the teachers’ perceptions within the boundaries of light setting selection and classroom context. Pattern recognition analysis shed light on how to make use of all four settings of the dynamic light system.